Impact of Loneliness on Brain Health and Quality of Life Among Adults Living With HIV in Canada. (1st August 2020) - Harris, Marianne; Brouillette, Marie-Josée; Scott, Susan C.; Smaill, Fiona; Smith, Graham; Thomas, Réjean; Fellows, Lesley K.; Mayo, Nancy E.
Abstract : Background: People aging with HIV are at risk for loneliness, with stigmatization and economic marginalization added to the health challenges arising from chronic infection. This study provides evidence for the extent, contributors, and consequences of loneliness in people living with HIV, focusing on brain health and quality of life. Setting: Cross-sectional data from 856 middle-aged and older adults living with HIV recruited from 5 urban specialty clinics in Canada were drawn from the inaugural visit of the Positive Brain Health Now cohort study. Methods: Participants completed an extensive assessment of biopsychosocial variables. The prevalence, severity, and quality of life impact of self-reported loneliness were described. Clinical and environmental factors hypothesized as contributing to loneliness, and the consequences of loneliness on health and function were identified using logistic, ordinal, and linear regression. Results: Eighteen percent reported being "quite often" and 46% "sometimes" lonely. Those with more loneliness were younger, less mobile, suffered more financial hardship, and were more likely to use opioids. HIV symptoms, pain, fatigue, low motivation, stigma, and unemployment were related to loneliness. Loneliness increased the odds of cognitive impairment, low mood, stress, and poor physical health. Those who were "quite often" lonely were over 4 times more likely to report poor or very poor quality of life than those who were "almost never" lonely. Conclusion: Loneliness is common in middle-aged and older people living with HIV in Canada. Many of the associated factors are modifiable, offering novel targets for improving brain health, general health, and quality of life in HIV.